The implementation of linguistic pedagogical activities using L1 reference background to foster L2 oral communicative competence among adult learners at CINDEA Judas, 2020 = La implementación de actividades lingüísticas pedagógicas usando como referencia el conocimiento de la lengua materna para el desarrollo de la competencia oral comunicativa en un segundo idioma en estudiantes adultos en CINDEA Judas, 2020 - Brenes Méndez, Vivian María 1993-; González Hernández, Diego Emmanuel 1993-; Rojas Rojas, Lilieth Viviana 1990-; Solórzano Madrigal, Karol Daniela 1993-; Chacón Prado, Mónica de Jesús 1981- ([Puntarenas, Costa Rica], 2021)
The use of the mother tongue in the English class has been a controversial topic in the education field. Therefore, this study is aimed to analyze the implementation of linguistic pedagogical activities using L1 reference background to foster L2 oral communicative competence among adult learners at CINDEA Judas, 2020. For carrying out this objective, there was selected one control and one experimental group, considering a sample of six and ten participants, respectively. Moreover, five linguistic pedagogical activities were applied to foster learners' oral communication in the target language: English. Thereby, five instruments were designed to collect the information. First, a diagnostic test was applied to gather students' starting English level; referencing their scores to the CEFRL parameters. Second, a Likert scale to evaluate participants' performance during the activities. Third, a post-test presented the effectiveness of the activities. Fourth, one survey was done to the participating students and one interview to the collaborating teacher to gather their opinion regarding the activities. Lastly, the results were analyzed in a triangulation chart; the outcomes were supported by findings of other researchers and the English Study Program proposed by MEP (2016.) Consequently, the findings from the current research showed that participants' English level increased; specifically, they got an upgrade on their scores. In the diagnostic test, most learners obtained a Beginner level, whereas in the post-test they all improved their grades, reaching an Elementary English level. In conclusion, the activities were implemented concerning a balance between English and Spanish; in fact, participants took advantage of this balance to increase their oral competence.
Proyecto de graduación (licenciatura en enseñanza del inglés)--Universidad de Costa Rica. Sede Regional del Pacífico Arnoldo Ferreto Segura. Departamento de Filosofía, Artes y Letras. Sección de Lenguas Modernas, 2021
El item presenta un leve error en la secuencia numérica (x-13) pero el contenido está completo
Keywords: COMPETENCIA COMUNICATIVA -- METODOS DE ENSEÑANZA; COMUNICACION ORAL; INGLES -- ESTUDIO Y ENSEÑANZA; EDUCACION DE ADULTOS; ADQUISICION DE UNA SEGUNDA LENGUA